ORIGIN OF THE CENTRAL ASIAN MOUNTAIN BELT: COLLISION OR MANTLE DIAPIRISM - Khain V.E. (My University, 1990)
The origin of the Central Asiatic mountain belt is treated nowadays from two opposing points of view. Some researchers believe that it is a consequence of the collision of the Indo-Australian and Eurasian lithospheric plates, starting from the Late Eocene; others consider the mountain edifices of this belt to be the product of low-density mantle uplift. Analysis of these concepts leads the author to the conclusion that they are not mutually exclusive, taking into account that both are based on actually observed facts: deformations connected with general compression in the first instance, and the elevated position of low-velocity rocks in the second. But the primary and main mechanism was the collision of the main tectonic plates, and heating of the lower part of the lithosphere and the formation of asthenospheric lenses represent a secondary effect. The processes of plate collision and mountain building were periodically repeated during the pre-Cenozoic history of Central Asia.
Keywords: Eocene; Cenozoic; Кайнозой::Палеоген::Эоцен; Cenozoic; Cenozoic::Paleogene::Eocene; Кайнозой